Debt overhang and investment efficiency - Francesca Barbiero; Alexander Popov; Marcin Wolski (European Investment Bank (EIB), 2018)
Using a pan-European data set of 8.5 million firms, this paper finds that firms with high debt overhang invest relatively more than otherwise similar firms if they are operating in sectors facing good global growth opportunities. At the same time, the positive impact of a marginal increase in debt on investment efficiency disappears if firm debt is already excessive, if it is dominated by short maturities, and during systemic banking crises. The results are consistent with theories of the disciplining role of debt, as well as with models highlighting the negative link between agency problems at firms and banks and investment efficiency.
Keywords: E22; E44; G21; H63; 330; Investment effciency; Debt overhang; Banking crises